Exploring Nurses' Perceptions of Disaster Preparedness Competencies - Wiwin Winarti; Naomi Gracya (Department of Nursing, Faculty of Medicine, Diponegoro University, 2023)
Background: Indonesia frequently experiences natural disasters, underscoring the importance of nursing competencies in disaster preparedness. Nevertheless, especially among general nurses, the factors shaping these competencies are not well understood.Purpose: This study aimed to explore Indonesian nurses’ perceptions of disaster preparedness competencies and compare these perceptions across distinct characteristics.Methods: Adopting a cross-sectional design, 230 nurses from all wards of a public hospital in Jakarta Province were selected via quota sampling. The Nurses’ Perceptions of Disaster Core Competencies Scale (NPDCC) questionnaire was utilized to assess nurses’ perceptions of competencies across five domains. The study employed Chi-square, Fisher’s exact, and Likelihood ratio tests, followed by backward (likelihood ratio) multiple logistic regression, to analyze the relationship between nurses’ characteristics and their perception of disaster preparedness competencies.Results: Results indicated that 51.7% of nurses perceived their disaster competencies as high, with an average score of 175.84(25.017). Further analysis revealed that nurses’ perceptions of these competencies were influenced by education (p=0.002), disaster simulation experience (p=0.036), and awareness of hospital disaster plans (p=0.012), with Nagelkerke’s R2=0.140. Nurses with a diploma qualification were 2.569 times more likely to perceive their skills as lower. Lack of simulation experience and unawareness of the plan further diminished perceived competencies, with ORs of 2.050 and 5.420, respectively.Conclusion: While education, disaster simulation experience, and plan awareness are crucial for nurses’ perceptions of disaster competencies, enhancing other supportive factors is also vital. This study recommends that hospitals increase educational opportunities, emphasizing regular disaster simulations and granting better access to disaster plans, to bolster nurses’ disaster preparedness competencies.